(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Il cambio di paradigma indotto dalla pandemia - 2. Complessità sociali e complessità giuridiche: le loro scansioni temporali - 3. L’obiettivo di “vivere insieme in una società democratica” - 4. L’esemplare negativo della pronunzia S.A.S. c. Francia - 5. La critica alla “cecità interculturale” del secolarismo - 6. La “laicità all’europea” e il principio del “dualismo giurisdizionale” - 7. L’apporto degli ecclesiasticisti: il contributo dell’ ‘accademia’ a una politica del diritto più inclusiva - 8. Il ritorno in auge dei paradigmi euro-mediterranei e gli sviluppi delle democrazie pluraliste. Cross-cultural Dialogue and Religious Minority in Europe at the COVID-19’s time. The Contribution of the Ecclesiasticists. ABSTRACT: The spread of the pandemic COVID-19, together with the measures of social distance and lockdown, paradoxically have contributed to making the need to recognize what is in common between the most diverse realities increasingly felt. Europe has greater legal resources than other regions of the world to ensure genuine cross-cultural and pluralistic development of the democratic systems.